Creative Techniques To Develop The Entrepreneurship’s Skills And Performance: Case Of Abu Tlemcen’s Entrepreneurship House - Ziane Kolee, Imene (جامعة الوادي - University of Eloued, 2021)
The objective of this study is to examine the impact of entrepreneurship‟s creative techniques training on the development and enhancement of entrepreneurial skills that may be essential to improve ventures effectiveness. We conducted a selective exploratory survey with 80 futur entrepreneurs. We strived towards a deeper understanding of the programs and tried to identify a link between Creative Techniques and entrepreneurial activities. SPSS was used to analyze the data gathered. Findings from the study reveal that the behavioral component of the students' attitude toward entrepreneurship‟s creative techniques training was positive. The data demonstrates that the entrepreneurship‟s creative techniques training appear to create openness, confidence, and trust among the participants in this study.
مقال
Keywords: entrepreneurship ; creative techniques ; entrepreneur ; skills ; performance